A New Method for Quantifying Platelet Deposition in Flowing Native Blood in an Ex Vivo Model of Human Thrombogenesis - Bossavy, J. P.; Sakariassen, K. S.; Barret, A.; Boneu, B.; Cadroy, Y. (Thrombosis and Haemostasis, 1998)
No quantitative, simple and non-radioactive method has been described for measuring the platelet content of experimental thrombi. The aim of the present study was to develop a simple method for quantifying platelets in thrombi formed on thrombogenic surfaces in flowing native human blood. To test the relevance of this new method, the effect of unfractionated heparin on arterial thrombus formation was investigated. Tissue factor (TF)- and collagen-coated coverslips were exposed to non-anticoagulated blood at an arterial wall shear rate (2,600 s–1) for 1 to 4 min. Platelet deposition was quantified by measuring the P-selectin (PS) and β-thromboglobulin (βTG) content of dissolved plasmin-digested thrombi using immunoenzymoassays; fibrin deposition was determined by measuring the D-dimer levels. These results were compared to those established by morphometrical analysis.Morphometric evaluation showed that fibrin deposition was maximum on TF by 1 min perfusion time. Platelets deposited subsequently and reached a maximum at 3 min. On collagen, platelets deposited directly on the collagen fibrils without detectable fibrin deposit. Platelet deposition increased from 1 to 4 min. Platelet deposition quantified by PS was correlated to the values obtained by morphometry (r = 0.72, r = 0.67, p <0.001, on TF and collagen, respectively). As compared to PS, βTG measurements gave an underestimation of the size of the thrombus platelet number. Unfractionated heparin infused through a mixing device proximal to the perfusion chamber to obtain plasma concentrations of 0.5, 1 and 3 IU/ml, reduced fibrin deposition on TF-coated coverslips in a dose-dependent manner (77% reduction at 3 IU/ml, p <0.01), but had no significant effect on platelet deposition (33% at 3 IU/ml, p >0.05). In contrast, heparin had no effect on fibrin or platelet deposition on collagen-coated coverslips.Thus, a new quantitative and simple method for measuring platelet deposition in flowing blood has been developed and characterized. Utilizing this system, we have demonstrated that unfractionated heparin did not inhibit arterial thrombus formation either on procoagulant or on proaggregant surface.